Applicability of the real ear measurement for audiological intervention of tinnitus, - Rocha,Andressa Vital (2020)
Abstract Introduction Tinnitus is present in a large part of chronic health complaints, and it is considered a public health problem injurious to the individual's quality of life. Considering the increase of the world population associated with an increase of life expectancy, tinnitus remains a cause for medical concern, since during aging the occurrence of auditory impairments due to the deterioration of the peripheral auditory structures and central impairs the quality of life. Objective The aim of the present study was to analyze the applicability of real ear measurements for audiological intervention of tinnitus through specific evaluation, selection, verification and validation of the hearing aids combined with the sound generator. Methods Forty individuals of both genders with hearing loss and tinnitus complaints were deemed eligible to compose the sample. They were enrolled according to clinical symptoms and submitted to the following procedures: anamnesis and previous complaint history, high frequency audiometry, immittanciometry and acuphenometry with the research of psychoacoustic thresholds of pitch, loudness and minimum masking threshold, sound generator, in addition to the application of the Tinnitus Handicap Inventory and Visual Analog Scale tools. The entire sample was adapted with Siemens hearing aids and a sound generator, participated in a counseling session with support of digital material and evaluated in two situations: Initial Assessment (before the hearing aids and sound generator adaptation) and Final Assessment (6 months, after adaptation). The statistical analyzes were descriptive and inferential, adopted a significance level of 5% and the T-Paired Test and the Spearman Correlation test were performed. Results The results showed that there was a benefit with the use of hearing aids combined with a sound generator from the statistically significant values and strong correlations between the sound generator verification data regarding acuphenometry and the nuisance/severity questionnaires. Regarding the verification of the sound generator, it is important to highlight that the entire sample selected the effective acoustic stimulation based on the comfort levels, which was proved in the present study to be a sufficient intensity for positive prognosis, whereas the users' noises were found below the psychoacoustic thresholds of acuphenometry. Conclusion The present study concluded that the audiological intervention with any level of sound stimulus is enough to obtain a positive prognosis in the medium term. Data that specifies that the verification of sound generator was effective at the real ear measurements are important in the evaluation and intervention of the complaint. In addition, it points out that the greater the tinnitus perception, the greater its severity, and the greater the nuisance, the higher the psychoacoustics thresholds of frequency and the minimum threshold of masking.